PENGEMBANGAN E-MODUL BERBANTUAN BOOK CREATOR PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR GUGUS I KECAMATAN LUBUK BEGALUNG KOTA PADANG - Apriwati, Resi; Mansrudin; Reinita; Amini, Risda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem arising from the lack of innovation in Pancasila Education Learning, where the use of teaching materials is still limited to printed forms and the minimal use of digital technology has the potential to hinder the achievement of learning objectives, especially in realizing the Pancasila Student Profile. Therefore, the purpose of this study is to develop a valid, practical, and effective e-module assisted by Book Creator in Pancasila Education Learning in Grade V of Elementary Schools so as to improve student understanding and involvement in the learning process. This type of research is research and development (Research and Development) with the ADDIE development model. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The Trial Subject was conducted at SDN 36 Cengkeh, then continued with research at SDN 30 Cengkeh and implemented at SDN 18 Kampung Baru for fifth grade elementary school students. The results of the research on the development of E-Modules Assisted by Book Creator in Pancasila Education Learning in Fifth Grade Elementary School are valid with an overall validation percentage of 92.95% in the Very Valid category. For the overall results of teacher practicality, the percentage obtained was 90.52% in the Very Practical category and the overall results of student practicality obtained a percentage of 91.70% in the Very Practical category. In addition, this E-Module assisted by Book Creator has also proven effective in improving student learning outcomes on the material "Various Norms in My Life". Based on the results of this study, it can be concluded that the E-Module Assisted by Book Creator in Pancasila Education Learning in Fifth Grade Elementary School is declared valid, practical and effective for use in the learning process. Keywords: ADDIE, Book Creator, E-Module, Pancasila Education